Evaluating hydrological components and streamflow characteristics under conventional and adaptive multi‐paddock grazing management. (8th February 2022) - Kim, JungJin; Ale, Srinivasulu; Teague, W. Richard; Wang, Tong
Abstract: Enhancing ecosystem services and improving water catchment functions are significant components of sustainable rangeland management. Different grazing management practices including the continuous season‐long heavy stocking (HS) and light stocking (LS), and adaptive multi‐paddock stocking (MPS) are adopted on rangelands around the world. Studies evaluating the effects of grazing management practices on streamflow characteristics are lacking. In this study, the Soil and Water Assessment Tool was used to assess the impacts of HS (24 Animal Units [AU] per 100 ha), LS (12 AU/100 ha), and adaptive MPS (24 AU/100 ha) management practices on hydrological conditions and streamflow characteristics in the Lower Prairie Dog Town Fork Red River watershed in north Texas. The model was calibrated based on 36 years of measured daily streamflow data and then used to assess the variation in hydrological components and streamflow characteristics under different grazing management practices, and no grazing (EX). Results indicated that the adaptive MPS decreased surface runoff by 30.6 and 46.0%, streamflow by 15.6 and 23.6%, and Richards–Baker flashiness Index by 24.1 and 35.9%, while increasing Baseflow Index by 19.7 and 31.6% when compared to the continuous LS and HS, respectively. In addition, changing grazing management from HS or LS to MPS showed a general tendency to decrease the magnitude of high flows and increase the magnitude of low flows, thereby decreasing the frequency of occurrence of floods and droughts. Simulated hydrologic conditions under MPS and EX scenarios were similar. Overall, adaptive MPS was found to be an ideal grazing management practice for water conservation, streamflow stability, and reduction of flood and drought risk.